Oxide formation on NiTi surface : influence of the heat treatment time to achieve the shape memory - Hansen, Alana Witt (2016)
Several studies regarding superficial treatments of Nitinol (NiTi) shape-memory have been developed aiming to the improve corrosion resistance and to block the Ni release to adjacent tissues. The necessary heat treatment to achieve the shape memory effect normally occurs at temperatures between 500 and 600 °C. However, titanium oxide (TiO2) is formed on the NiTi surface during the shape memory process heat treatment. In this work the effects of the heat treatment time on the surface characteristics of the formed NiTi oxide, at temperatures that promote the shape-memory (530 and 570 °C), were evaluated. The TiO2 layers which were obtained were evaluated by X-ray diffraction (XRD), energy dispersive X-ray (EDX), scanning electron microscope (SEM), thermogravimetric analysis (TGA), wettability and roughness. The results show that by increasing the exposure time at the temperature of 570 °C the formation of a thicker oxide is promoted, with less superficial roughness and of a hydrophobic nature. According to the literature, these characteristics indicate that the obtained oxide layer has properties that accelerat the osseointegration process.